1992
DOI: 10.1128/iai.60.2.529-535.1992
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of a Serpula (Treponema) hyodysenteriae hemolysin gene

Abstract: Serpula (Treponema) hyodysenteriae, the etiologic agent of swine dysentery, produces a hemolysin which is thought to be an important factor in the pathogenesis of the disease. We report the cloning, sequencing, and expression of a hemolysin gene (tly) from S. hyodysenteriae B204. A pUC19 gene bank of strain B204 was constructed in the Escherichia coli K-12 strain DH5a, and hemolytic recombinants were identified by plating the library on blood agar plates. From the hemolytic recombinants, a 1.5-kb DNA fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…The Serpula (Treponema) hyodysenteriae hemolysin homolog genes (e.g. tlyA and tlyC) (Muir et al, 1992;Hsu et al, 2001) were recently demonstrated in other pathogenic bacterial species (e.g. Rickettsia, Helicobacter, and Salmonella) (Martino et al, 2001;Whitworth et al, 2005), and TlyC from R. typhi was shown to be functional and to also possess hemolytic activity (Radulovic et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The Serpula (Treponema) hyodysenteriae hemolysin homolog genes (e.g. tlyA and tlyC) (Muir et al, 1992;Hsu et al, 2001) were recently demonstrated in other pathogenic bacterial species (e.g. Rickettsia, Helicobacter, and Salmonella) (Martino et al, 2001;Whitworth et al, 2005), and TlyC from R. typhi was shown to be functional and to also possess hemolytic activity (Radulovic et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment is hampered by a limited number of e¡ective antibiotics and an increasing number of resistant strains [3], and vaccination with whole-cell bacterins is not e¡ective [4]. Research concerning potential virulence factors of B. hyodysenteriae has focussed on motility [5] and motility-associated genes [6] as well as on di¡erent hemolysins (tlyA [7], tlyB and tlyC [8], and hlyA [9]). In addition, the NADH oxidase [10] and several surface-associated proteins have been identi¢ed [11], and a physical and genetic map of B. hyodysenteriae B78 T has been constructed [12].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment is hampered by a limited number of effective antibiotics and an increasing number of resistant strains[3], and vaccination with whole‐cell bacterins is not effective[4]. Research concerning potential virulence factors of B. hyodysenteriae has focussed on motility[5] and motility‐associated genes[6] as well as on different hemolysins ( tly A[7], tly B and tly C[8], and hly A[9]). In addition, the NADH oxidase[10] and several surface‐associated proteins have been identified[11], and a physical and genetic map of B. hyodysenteriae B78 T has been constructed[12].…”
Section: Introductionmentioning
confidence: 99%